Membangun Kesadaran Siswi tentang Pelecehan Seksual di Media Sosial - Tunjung Bayu Sinta; Hanifah Hanifah; Noor Lita Sari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Technological advances have led to an increase in the need for information and communication flows, as currently developing smartphones. Social media is an application that can connect one individual to another using the internet. The use of the internet has both positive and negative impacts, one of the negative impacts is the ease with which acts of sexual harassment occur. The average victim is a woman. Based on data in Karanganyar Regency for 2021, it is known that there are still cases of sexual harassment of female victims. This service activity was carried out at Muhammadiyah Darul Arqom Karanganyar High School for male and female students of class X by providing material about sexual fading on social media. The purpose of this community service activity is to build students' self-awareness about sexual harassment on social media, such as forms of social media sexual harassment, its causes, and how to prevent it.